Modulation of Mitochondrial Quality Control Processes by BGP-15 in Oxidative Stress Scenarios: From Cell Culture to Heart Failure. (28th February 2021) - Horvath, Orsolya; Ordog, Katalin; Bruszt, Kitti; Kalman, Nikoletta; Kovacs, Dominika; Radnai, Balazs; Gallyas, Ferenc; Toth, Kalman; Halmosi, Robert; Deres, Laszlo
Abstract : Heart failure (HF) is a complex chronic clinical disease characterized by among others the damage of the mitochondrial network. The disruption of the mitochondrial quality control and the imbalance in fusion-fission processes lead to a lack of energy supply and, finally, to cell death. BGP-15 (O-[3-piperidino-2-hydroxy-1-propyl]-nicotinic acid amidoxime dihydrochloride) is an insulin sensitizer molecule and has a cytoprotective effect in a wide variety of experimental models. In our recent work, we aimed to clarify the mitochondrial protective effects of BGP-15 in a hypertension-induced heart failure model and "in vitro." Spontaneously hypertensive rats (SHRs) received BGP-15 or placebo for 18 weeks. BGP-15 treatment preserved the normal mitochondrial ultrastructure and enhanced the mitochondrial fusion. Neonatal rat cardiomyocytes (NRCMs) were stressed by hydrogen-peroxide. BGP-15 treatment inhibited the mitochondrial fission processes, promoted mitochondrial fusion, maintained the integrity of the mitochondrial genome, and moreover enhanced the de novo biogenesis of the mitochondria. As a result of these effects, BGP-15 treatment also supports the maintenance of mitochondrial function through the preservation of the mitochondrial structure during hydrogen peroxide-induced oxidative stress as well as in an "in vivo" heart failure model. It offers the possibility, which pharmacological modulation of mitochondrial quality control under oxidative stress could be a novel therapeutic approach in heart failure.